EjTFL1 Genes Promote Growth but Inhibit Flower Bud Differentiation in Loquat - Jiang, Yuanyuan; Zhu, Yunmei; Zhang, Ling; Su, Wenbing; Peng, Jiangrong; Yang, Xianghui; Song, Huwei; Gao, Yongshun; Lin, Shunquan (Frontiers in Plant Science, 2020)
TERMINAL FLOWER1 (TFL1), a key factor belonging to the phosphatidyl ethanolamine-binding protein (PEBP) family, controls flowering time and inflorescence architecture in some plants. However, the role of TFL1 in loquat remains unknown. In this study, we cloned two TFL1-like genes (EjTFL1-1 and EjTFL1-2) with conserved deduced amino acid sequences from cultivated loquat (Eriobotrya japonica Lindl.). First, we determined that flower bud differentiation occurs at the end of June and early July, and then comprehensively analyzed the temporal and spatial expression patterns of these EjTFL1s during loquat growth and development. We observed the contrasting expression trends for EjTFL1s and EjAP1s (APETALA 1) in shoot apices, and EjTFL1s were mainly expressed in young tissues. In addition, short-day and exogenous GA3 treatments promoted the expression of EjTFL1s, and no flower bud differentiation was observed after these treatments in loquat. Moreover, EjTFL1s were localized to the cytoplasm and nucleus, and both interacted with another flowering transcription factor, EjFD, in the nucleus, and EjTFL1s-EjFD complex significantly repressed the promoter activity of EjAP1-1. The two EjTFL1s were overexpressed in wild-type Arabidopsis thaliana Col-0, which delayed flowering time, promoted stem elongation, increased the number of branches, and also affected flower and silique phenotypes. In conclusion, our results suggested that EjTFL1-1 and EjTFL1-2 do not show the same pattern of expression whereas both are able of inhibiting flower bud differentiation and promoting vegetative growth in loquat by integrating GA3 and photoperiod signals. These findings provide useful clues for analyzing the flowering regulatory network of loquat and provide meaningful references for flowering regulation research of other woody fruit trees.